Iron regulation in athletes: Exploring the menstrual cycle and effects of different exercise modalities on hepcidin production - Sim, M.; Dawson, B.; Landers, G.; Trinder, D.; Peeling, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
The trace element iron plays a number of crucial physiological roles within the body. Despite its importance, iron deficiency remains a common problem among athletes. As an individual`s iron stores become depleted, it can affect their well-being and athletic capacity. Recently, altered iron metabolism in athletes has been attributed to postexercise increases in the iron regulatory hormone hepcidin, which has been reported to be upregulated by exercise-induced increases in the inflammatory cytokine interleukin-6. As such, when hepcidin levels are elevated, iron absorption and recycling may be compromised. To date, however, most studies have explored the acute postexercise hepcidin response, with limited research seeking to minimize/attenuate these increases. This review summarizes the current knowledge regarding the postexercise hepcidin response under a variety of exercise scenarios and highlights potential areas for future research—such as: a) the use of hormones though the female oral contraceptive pill to manipulate the postexercise hepcidin response, b) comparing the use of different exercise modes (e.g., cycling vs. running) on hepcidin regulation.